Higher Order Backlund Transformation for u_t+uu_x+α u-u_xx+γ u_xxx+u_yy = 0 - S. Padmasekaran; S. Lavanya Devi; G. Sivagami (International Journal of Mathematics And its Applications, 2016)
The homogeneous balance (HB) method has drawn lots of interests in seeking the solitary wave solution and other kinds of solutions. Wang showed the HB method is powerful for finding analytic solitary wave solutions of PDE. In this paper, the solitary wave solution of nonlinear PDE has been obtained by this method.